1999
DOI: 10.1097/00003246-199906000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lower limb pneumatic compression on pulmonary artery temperature

Abstract: Intermittent pneumatic calf compression increased lower limb venous return, causing acute but transient decreases in pulmonary artery blood temperature. This did not affect the accuracy of thermodilution cardiac output measurements that were made using 10 mL of either cold or room temperature injectate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
1
11
1
Order By: Relevance
“…Possible explanations for the apparent disparity between our results and that of Horiuchi et al (20), who failed to demonstrate significant changes in CO with pneumatic calf compression, concern two key differences: the type of pneumatic compression device used and the timing of CO determinations. In the study by Horiuchi et al (20), NCDs were used, whereas we used SCDs that inflate sequentially from the ankle toward the knee.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Possible explanations for the apparent disparity between our results and that of Horiuchi et al (20), who failed to demonstrate significant changes in CO with pneumatic calf compression, concern two key differences: the type of pneumatic compression device used and the timing of CO determinations. In the study by Horiuchi et al (20), NCDs were used, whereas we used SCDs that inflate sequentially from the ankle toward the knee.…”
Section: Discussioncontrasting
confidence: 99%
“…The second key difference is in the timing of CO measurements in relation to the inflation cycle of the device, which may affect CO determination. The exact timing of CO measurement in the Horiuchi et al (20) study is not explicitly indicated. In our study, the timing of CO determinations occurs at two specific points in the inflation cycle, 2-4 secs (T2) and 4 -8 secs (T3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations